2005
DOI: 10.1007/s10162-005-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Suppression in the Upward Spread of Masking

Abstract: The upward spread of masking refers to the higher growth rate of masking for maskers lower in frequency than the signal, compared to maskers at the signal frequency (Wegel RL, Lane CE. The auditory masking of one pure tone by another and its possible relation to the dynamics of the inner ear. Physics Rev. 23:266-285, 1924; Egan JP, Hake HW. On the masking pattern of a simple auditory stimulus. J. Acoust. Soc. Am. 22:622-630, 1950; Delgutte B. Physiological mechanisms of psychophysical masking: Observations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
2
7
2
Order By: Relevance
“…With respect to the MOCR, there is at least one reason why simultaneous masking additivity for the Gaussian stimuli used in the present study may differ from that observed in the cited studies of masking additivity (Humes et al, 1992) and USSM (Oxenham and Plack, 1998;Bacon et al, 1999;Yasin and Plack, 2005). All those studies involved relatively long maskers and presented the target at the temporal center of the masker, while the Gaussians used in the present study had a very short duration (<10 ms).…”
Section: Introductioncontrasting
confidence: 68%
See 3 more Smart Citations
“…With respect to the MOCR, there is at least one reason why simultaneous masking additivity for the Gaussian stimuli used in the present study may differ from that observed in the cited studies of masking additivity (Humes et al, 1992) and USSM (Oxenham and Plack, 1998;Bacon et al, 1999;Yasin and Plack, 2005). All those studies involved relatively long maskers and presented the target at the temporal center of the masker, while the Gaussians used in the present study had a very short duration (<10 ms).…”
Section: Introductioncontrasting
confidence: 68%
“…For target-masker frequency ratios and target levels approximately comparable to our condition M2M3, masking growth rates of about 2.0 (Oxenham and Plack, 1998;Bacon et al, 1999) to 2.5 dB/dB (Yasin and Plack, 2005) have been reported. Considering the average rate of 2.2 dB/dB across these studies and assuming intensity summation of the individual masker excitations would lead to excess masking for a masker pair of (3 Â 2.2) À 3 ¼ 3.6 dB.…”
Section: Comparison To the Literaturementioning
confidence: 77%
See 2 more Smart Citations
“…Behavioral measures often infer cochlear compression by estimating the cochlear input/ output (I/O) function, which exhibits linear growth at low levels and compressive growth at mid to high levels (e.g., Ruggero and Rich 1991). Compression can be estimated from masking data by calculating the minimum slope of the derived I/O function (Yasin and Plack 2005) or by fitting a linear function to the data above the breakpoint that separates the linear and compressive regions (Yasin and Plack 2003). Temporal masking curves (TMCs) have gained acceptance as a behavioral measure for estimating cochlear compression in adults with normal and impaired hearing (Nelson et al 2001).…”
Section: Introductionmentioning
confidence: 99%